THERAPEUTIC POTENTIAL OF PEGNUM HARMELA AGAINST SCHISTOSOMA BOVIS IN BUFFALOES - Niaz, Sadaf; Akhter, Tanveer; AbdEl-Salam, Naser M.; Ayaz, Sultan; Shams, Sumaira; Ullah, Riaz; Hussain, Hidayat; Bibi, Safia (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Peganum harmala have many biological and pharmacological activities such as antifungal, antibacterial, analgesic and antiinflammatory.The present study was carried out to evaluate the antischistosomal activities of Peganum harmala with special reference to bovineschistosomiasis in naturally infected buffaloes.Methods and Materials: A total of 54 naturally infected buffaloes with “Schistosomiasis” of ages around five years were used for anthelminticstudies. All of the buffaloes were properly marked so as to make a distinction from one other. A doctor of veterinary was available for daily checkup.Samples prepared according to the available methods in literature.Results: In the present study, naturally infected buffaloes with Schistosoma bovis were treated with Peganum harmala (Harmal, seed), with dose 75mg/kg, 150 mg/kg and 225 mg/kg body weight respectively, and their impact on various parameters like eggs reduction, milk production, weight gainand feed intake was noted. Furthermore, their efficiency (%) was evaluated with “Praziquantel” (allopathic drug) at “10mg/Kg body weight” doselevel. After first dose of “Praziquantel” hundred percent effectiveness was noted, while the same result obtained for herbal drug after giving seconddose of “225mg/kg body weight”. To evaluate the effect of herbal medicines on protein portions, sera of treated and control buffaloes were alsoinvestigated.Conclusion: From present findings, it is concluded that the herb Peganum harmala can easily replace Praziquantal (PZQ) with almost sameefficiency (%). Furthermore, the herb is easily available at cheap price at local market and it will be good for the economy of Pakistan